Reduced GABAergic neuropil and interneuron profiles in schizophrenia: Complementary analysis of disease course-related differences. (January 2022) - Förster, Antonia; Model, Vera; Gos, Tomasz; Frodl, Thomas; Schiltz, Kolja; Dobrowolny, Henrik; Meyer-Lotz, Gabriela; Guest, Paul C.; Mawrin, Christian; Bernstein, Hans-Gert; Bogerts, Bernhard; Schlaaff, Konstantin; et al.
Abstract: Background: GABAergic interneuron dysfunction has been implicated in the pathophysiology of schizophrenia. Expression of glutamic acid decarboxylase (GAD), a key enzyme in GABA synthesis, may also be altered. Here, we have simultaneously evaluated GAD-immunoreactive (GAD-ir) neuropil and cell profiles in schizophrenia-relevant brain regions, and analysed disease-course related differences. Methods: GAD65/67 immunoreactivity was quantified in specific brain regions for profiles of fibres and cell bodies of interneurons by automated digital image analysis in post-mortem brains of 16 schizophrenia patients from paranoid (n = 10) and residual (n = 6) diagnostic subgroups and 16 matched controls. Regions of interest were superior temporal gyrus (STG) layers III and V, mediodorsal (MD) and laterodorsal (LD) thalamus, and hippocampal CA1 and dentate gyrus (DG) regions. Results: A reduction in GAD-ir neuropil profiles (p < 0.001), particularly in STG layer V (p = 0.012) and MD (p = 0.001), paralleled decreased GAD-ir cell profiles (p = 0.029) in schizophrenia patients compared to controls. Paranoid schizophrenia patients had lower GAD-ir neuron cell profiles in STG layers III (p = 0.007) and V (p = 0.001), MD (p = 0.002), CA1 (p = 0.001) and DG (p = 0.043) than residual patients. There was no difference in GAD-ir neuropil profiles between paranoid and residual subgroups (p = 0.369). Conclusions: These results support the hypothesis of GABAergic dysfunction in schizophrenia. They show a more prominent reduction of GAD-ir interneurons in paranoid versus residual patients, suggestive of more pronounced GABAergic dysfunction in the former. Fully automated analyses of histological sections represent a step towards user-independent assessment of brain structure.